A Case Study on Feed Management to Improving Production and Economic Returns for the Semi-Intensive Pond Production of Litopenaeus vannamei - Allen Davis, D.; Amaya, Elkin; Venero, Jesus; Zelaya, Oscar; B. Rouse, David (Facultad de Ciencias Biologicas, 2019)
Feed represent one of the primary costs associated with the production of shrimp under semi-intensive and intensiveconditions. The feed is also the initial source of pollutants; hence, overfeeding or poor quality feeds can severelyimpact water quality and production. In order to improve production of shrimp under semi-intensive conditions andreduce waste outputs it is critical to optimize feed allowance and to develop appropriate feeding management plans.Despite the importance of feed management from both economic and environmental perspectives, there is relativelylittle scientific information regarding feed management. It is also quite interesting to note that almost allmanagement set points (e.g. poor growth, or good growth) result in increases in feed input and that most often oneof the lowest payed employee is responsible for the proper application of the most costly component of shrimpculture, (i.e. the feed). Over the last six years, research at the Claude Petite Mariculture Center has been conductedusing standardized operational protocols (35 shrimp/meter, 10 hp/ha of base aeration, limited water exchange) whileachieving a systematic improvement in feed management. This paper discusses from a historical perspective thesystematic improvement in feed management that have allowed us to improve feed utilization and total productionfrom typical feed conversion ratios (FCR, feed inputs per unit of shrimp harvested) of around 2:1 to 1.2-1.4:1 withincreases in overall production from around 4,000 kg/ha to 6,000kg/ha. These improvement in FCR have resultedin significant reductions in feed costs and subsequent improvement on the return on investment.